First evidence of hepatitis E virus in domestic pigs: a cross-sectional seroepidemiological study in the Bosnia and Herzegovina - Muftić, Abdullah (Frontiers in Veterinary Science, 2025)
IntroductionHepatitis E virus (HEV) is foodborne zoonotic pathogen widespread among European swine yet unstudied in Bosnia and Herzegovina (B&H). We estimated HEV seroprevalence in domestic pigs in Federation of B&H (FB&H) and assessed farm-level risk factors for exposure.MethodsCross-sectional survey sampled 437 pigs from 87 farms across seven cantons via two-stage random design. Serum anti-HEV IgG measured by commercial indirect ELISA; managers completed standardized biosecurity/management questionnaire. Apparent seroprevalence calculated with 95% CIs. Univariable screening (α = 0.10) informed multivariable logistic regression with farm-level clustering; collinearity checked (Phi), AIC-guided forward selection applied.ResultsAnimal-level seroprevalence 77.1% (95% CI 73.0–81.0%); herd-level 95.4% (88.9–98.7%). Adults showed higher seropositivity than growers (91.0% vs. 71.7%; p < 0.001). Significant factors: wild-boar proximity (adjusted POR 3.11; p = 0.04), small farm size (18.35; p < 0.001), swill feeding (5.70; p = 0.03). Cleaning ≥5×/month strongly protective (0.01; p < 0.001). All surveyed cantons had positives; no equivocal ELISA results.DiscussionFindings indicate widespread HEV in FB&H swine with environmental, food-safety, and occupational implications. Older-animal pattern reflects cumulative exposure; small-farm context and wildlife interface likely sustain transmission, whereas frequent cleaning reduces risk. Strengthened biosecurity, wildlife exclusion, feed oversight (including prohibition/monitoring of swill feeding), and improved hygiene, should form basis of One Health interventions to mitigate potential zoonotic transmission via the pork production chain.